School Quality and the Gender Gap in Educational Achievement - Autor, David; Figlio, David; Karbownik, Krzysztof; Roth, Jeffrey; Wasserman, Melanie (American Economic Review, 2016)
Recent evidence indicates that boys and girls are differently affected by the quantity and quality of family inputs received in childhood. We assess whether this is also true for schooling inputs. Using matched Florida birth and school administrative records, we estimate the causal effect of school quality on the gender gap in educational outcomes by contrasting opposite-sex siblings who attend the same sets of schools–thereby purging family heterogeneity–and leveraging within-family variation in school quality arising from family moves. Investigating middle school test scores, absences and suspensions, we find that boys benefit more than girls from cumulative exposure to higher quality schools.